Pengujian Bending & Struktur Mikro Sambungan Temu Bahan AISI 1010 dgn Variasi Arus pd Pengelasan SMAW - Sutarto, Eko (SIMETRIS, 2024)
The aim of this research is to determine the flexural strength of AISI 1010 material which meets the ASME BPVC acceptance criteria. IX QW-163 bending test results using the face bend test method, observing the possibility of cracks on the tensile side of the surface of the test object using the dye penetrant test method and the possibility of changes in the microstructure of the joints in electric arc welding with a current of 70, 80 and 90 A with using E6013 electrodes with a diameter of 2.6 mm. From the results of the bending test, the average bending stress data obtained from welds with currents of 70, 80, and 90A were 973.67, 986.3, and 1,049.46 MPa respectively, while from the observation results there were no cracks on the tensile surface of the test object, and from the comparison of microphotographs before and after welding there is no significant change in microstructure.